Minimizing Waste to Reduce Lead Time Delivery at PT. X Through Value Stream Mapping Method - Danang Prihandoko (Faculty of Economics and Business, Jenderal Soedirman University, 2022)
The purpose of this study is to minimize waste in order to reduce lead time delivery at PT X. The method that the author uses in this research is a quantitative method with data analysis techniques using value stream mapping and seven waste analysis. The data collection technique that the author uses is interviews, observations, and company documents. The results of this study succeeded in reducing the lead time from 11 days, 31 hours 35 minutes, to 10 days, 23 hours 35 minutes if the operational unit is on standby. Furthermore, if the operational unit is on standby after 17 days 28 hours 35 minutes, it becomes 10 days 29 hours 35 minutes.